Using the TOP Model to Measure Program Performance: A Pocket Reference - Amy Harder (EDIS)
WC092, a 4-page illustrated fact sheet by Amy Harder, provides an overview of the Targeting Outcomes of Programs (TOP) Model of program planning and evaluation, defines the levels for assessing program performance, and identifies evaluation strategies appropriate for measuring program performance at each level. Includes references. Published by the UF Department of Agricultural Education and Communication, December 2009.